Upaya Meningkatkan Kemampuan Menulis Narrative Text Melalui Media Gambar Seri Sangkuriang pada Siswa Kelas IX SMP - Aswadi Aswadi (AL-BURHAN, 2022)
English is as media to communicate both orally and writing. The ability to communicate is the ability to understand and or produce spoken text and / or write are realized in the four language skills, ie listening, speaking, reading, and writing. Therefore, subjects in English is directed to develop such skills so that graduates are able to communicate in English both in writing and speaking. Hopefully the student able to communicate both orally or in writing, and their ability can be developed in a balanced way. But the reality of the ability to communicate verbally much lower than the ability to communicate in writing. This is evident from the data in SMP Negeri 2 Trangkil Pati Trangkil which indicates that the ability to write only 19.35% of students who have achieved mastery learning. For this study aims to determine the ability to write to the students of SMP Negeri 2 Trangkil Pati by conducting action research through the use of media image series voucher former so as the formulation of the problem is whether the use of media image series voucher former can improve the ability to write narrative text students and whether there are differences in the increase in the ability to write once held by the previous action. From the discussion of the results of this study can be concluded that the use of the media Sangkuriang pictures series improving writing skills narrative text. The indicator is the increasing average value, increasing the number of students who have achieved a minimum completeness and the total of the student who did not achieve a minimum completeness can be decreased.